Anatomical Variability of the Transverse and Sigmoid Sinus Grooves: Implications for Skull Base Surgery - Triantafyllou, George; Pishiaras, Harris; Papadopoulos-Manolarakis, Panagiotis; Paschopoulos, Ioannis; Tsakotos, George; Piagkou, Maria (Journal of Neurological Surgery Part B: Skull Base, 2025)
The transverse and sigmoid sinus grooves (TSGs and SSGs) contain the corresponding sinuses within the posterior cranial fossa. Bony groove morphology remains insufficiently studied, while venous sinus variants are well-documented. The present study investigates the morphological variability of TSG and SSG and their clinical implications.Ninety adult dried skulls were analyzed for the presence, width, and bony projections of the TSGs and SSGs. Emissary foramina (EF), including the mastoid emissary foramina (MEF) and posterior condylar canals (PCCs), were identified and measured. Statistical analysis assessed differences by side and sex, and correlations between groove dimensions were evaluated.The SSG was present bilaterally in all specimens. Incomplete bony projections were identified in 27.2% of SSGs, more commonly on the left (p = 0.029). TSG was absent from 19.4% of sides, with bony prominences present in 7.8%. MEF were observed in 48.3% of SSGs, and occipital emissary foramina (OEF) in 9.1% of TSGs. A strong positive correlation was found between the widths of the SSG and TSG (R = 0.506, p < 0.001).Significant morphological variability exists in the TSG and SSG, including bony bridges and EF. These features have direct surgical relevance, particularly in procedures such as retrosigmoid craniotomy, where accurate localization of venous structures is essential. Recognition of these variants is critical for surgical planning, minimizing intraoperative risk, and enhancing imaging interpretation in posterior cranial fossa and skull base approaches.
Keywords: transverse sinus; sigmoid sinus; transverse sinus groove; sigmoid sinus groove; emissary foramen; retrosigmoid approach; variation; skull base surgery